What the fact? : finding the truth in all the noise - Yasmin, Seema, 1982- (Simon & Schuster BFYR, 2022)
Examines the rise in fake news, propaganda, misinformation, and disinformation in modern-day media, and highlights the importance of media literacy. Includes black-and-white photographs.